Low yield ratio high ctod performance l485m pipeline steel hot-rolled coil and manufacturing method thereof

CN122879612APending Publication Date: 2026-10-09ANGANG STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611193703.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0009]综上所述,目前已公开的关于485MPa级管线钢的资料虽然较多,但在成分上多数依赖于合金元素Mo和Cr的添加;在韧性指标上多数仅进行冲击和落锤试验,对CTOD性能指标研究较少

Benefits of technology

1)采用Mg-Ca-La-Ti复合处理方法在钢中引入大量的纳米级氧化物粒子,阻碍铸坯加热和保温过程中奥氏体晶粒的长大,因而即使在较高的加热温度下也能获得细小的奥氏体晶粒,减轻了轧机负荷,有利于有粗轧大压缩比工艺的实施。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879612A_ABST
    Figure CN122879612A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of pipeline steel production, and particularly relates to a low-yield-ratio high-CTOD-performance L485M pipeline steel hot-rolled coil and a manufacturing method thereof. The chemical components in the steel are as follows in percentage by weight: C: 0.040%-0.060%, Si: 0.15%-0.25%, Mn: 1.60%-1.70%, P: ≤0.019%, S: ≤0.005%, Nb: 0.045%-0.055%, Ti: 0.012%-0.022%, Ni: 0.05%-0.10%, Als: 0.010%-0.020%, Ca: 0.002%-0.003%, Mg: 0.001%-0.002%, La: 0.002%-0.003%, N: ≤0.007%, and the balance being Fe and inevitable impurities. The yield strength of the hot-rolled coil is 520-580 MPa, the tensile strength is 650-710 MPa, the yield ratio is ≤0.80, the elongation is ≥30%, the average impact energy at-60 DEG C is ≥300 J, the average falling weight shear area at-40 DEG C is ≥90%, and the CTOD value at-40 DEG C is ≥1.60 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pipeline steel production technology, and in particular to a hot-rolled L485M pipeline steel coil with low yield strength ratio and high CTOD performance and its manufacturing method. Background Technology

[0002] With the continued growth of global energy demand, oil and gas pipelines are increasingly extending into harsh environments such as polar regions, deep seas, and earthquake-prone areas, placing more stringent demands on the comprehensive performance of pipeline steel. While traditional 485MPa grade pipeline steel can meet basic strength requirements, it often faces issues such as a high yield strength ratio, insufficient deformation capacity, and limited low-temperature toughness. A high yield strength ratio can lead to decreased pipeline safety in strain-based design areas (such as landslide areas and permafrost zones), and insufficient material reserve plastic deformation capacity during outages, pressure fluctuations, or unexpected impacts can easily lead to localized strain concentration, increasing the risk of failure. Furthermore, pipeline steel must possess excellent crack arrest toughness at low temperatures to prevent rapid crack propagation. Crack tip opening displacement (CTOD), as a key toughness indicator for evaluating a material's resistance to crack initiation and propagation, is crucial for ensuring the pipeline's resistance to brittle fracture.

[0003] Most existing patents focus on the impact and drop hammer performance of pipeline steel, with limited coverage of crack tip fracture density (CTOD), an indicator reflecting the actual fracture behavior at the crack tip. Particularly for thick hot-rolled coils, due to insufficient core deformation and microstructure differences, their CTOD values ​​are typically much lower than those at the surface, making it difficult to meet design requirements in low-temperature environments. Therefore, achieving a low yield strength ratio and high CTOD performance while maintaining the L485M strength grade through innovative composition design and process matching is a pressing issue in this field.

[0004] The following is a brief introduction to the patents and literature related to 485MPa grade pipeline steel that have been published domestically and internationally, but they are all significantly different from this invention, as detailed below: 1) Chinese patent document CN113278880A, L485MO, a low yield strength ratio and low hardness subsea pipeline steel, and its production method. The composition includes C: 0.060%~0.080%, Si: 0.10%~0.15%, Mn: 1.50~1.70%, P≤0.008%, S≤0.001%, Als: 0.015%~0.035%, Nb: 0.050%~0.060%, Ti: 0.005%~0.020%, and Mo: 0.10%~0.20%. This invention adds the precious metal element Mo to the alloy composition, making its composition completely different from that of this invention; at the same time, this invention requires a yield strength ratio not higher than 0.85, which is a relatively lenient requirement. Furthermore, the maximum thickness specification in the example is 20mm, which differs from the maximum thickness described in this invention.

[0005] 2) Chinese patent document CN111979497A, discloses a submarine pipeline steel plate coil with excellent low-temperature CTOD performance and a production process thereof. The composition comprises: C: 0.030%~0.070%, Si: 0.10%~0.20%, Mn: 1.10%~1.60%, Nb: 0.020%~0.050%, V: 0.020%~0.040%, Ti: 0.010%~0.030%, Mo: 0.10%~0.20%, Alt: ≤0.06%, P≤0.018%, S≤0.0080%. In the alloy composition design of the invention, the precious metal element Mo is added, so the composition is different from that of the present invention; meanwhile, the invention requires a yield strength of 453~510MPa and a tensile strength of 541~626MPa, which are relatively low strength indicators. In addition, after finish rolling, the invention only adopts laminar cooling and has a relatively high coiling temperature, so the production process is obviously different from that of the present patent.

[0006] 3) Chinese patent document CN116970870A, discloses a low yield ratio X70 grade pipeline steel hot rolled coil and a manufacturing method thereof. The composition comprises: C: 0.05%~0.08%, Si: 0.10%~0.30%, Mn: 1.40%~1.60%, Nb: 0.045%~0.065%, Ti: 0.010%~0.020%, Cr: 0.15%~0.25%, Mo: 0.08%~0.10%, Ni: 0.10%~0.20%, 0<P≤0.018%, 0<S≤0.0080%, Als: 0.015%~0.045%. In terms of composition, the invention adds relatively high contents of Mo and Cr, which is different from the present invention; meanwhile, the patent is mainly directed to thin-specification products of 9~13mm, and does not involve thick-specification products; in addition, the low-temperature toughness index of the invention is relatively loose, the impact test temperature is only -20°C, and the drop weight test temperature is only -15°C, which are far higher than those of the present patent.

[0007] 4) Chinese patent document CN115449709A, a thick-gauge high-strength and high-toughness L485M pipeline steel and its production method. The composition includes C: 0.05%~0.07%, Si: 0.15%~0.25%, Mn: 1.60%~1.80%, Nb: 0.060%~0.078%, Ti: 0.026%~0.032%, Mo: 0.12%~0.16%, Cr: 0.16%~0.20%, Ni: 0.11%~0.18%, Als: 0.015%~0.045%, P≤0.02%, S≤0.005%, N≤0.005%. This invention adds a higher content of Mo and Cr, which is significantly different from this patent; furthermore, the maximum thickness is 20mm, which differs from the maximum thickness described in this invention; additionally, this invention does not conduct relevant research on the yield strength ratio and CTOD.

[0008] 5) Chinese Patent Document CN117987741A, a high-performance X70M pipeline steel for thick-walled spiral submerged arc welded steel pipes and its manufacturing method. The composition includes C: 0.070%~0.080%, Si: 0.18%~0.28%, Mn: 1.60%~1.75%, P≤0.015%, S≤0.002%, V: 0.033%~0.043%, Nb: 0.080%~0.095%, Cr: 0.25%~0.35%, Als: 0.020%~0.050%, N≤0.005%. In terms of composition, this invention adds Cr, and the Nb and V contents are significantly higher than those of this invention, resulting in higher alloy costs. Simultaneously, this invention has relatively lenient yield strength ratio and low-temperature toughness indicators; the yield strength ratio of most embodiments is above 0.83, and the drop hammer test temperature is only -20℃.

[0009] In summary, although there is a considerable amount of publicly available information on 485MPa grade pipeline steel, most of it relies on the addition of alloying elements Mo and Cr in terms of composition; and in terms of toughness indicators, most of it only involves impact and drop hammer tests, with relatively little research on CTOD performance indicators.

[0010] This invention breaks with traditional pipeline steel alloy composition design. By introducing nanoscale oxide particles through Mg-Ca-La-Ti composite treatment, it inhibits austenite grain growth during billet heating and holding. In the rolling process, it increases the single-pass compression ratio of rough rolling and reduces the rolling speed, allowing sufficient dynamic recrystallization of austenite from the surface to the core. After rolling, a short relaxation time promotes the formation of a small amount of soft phase to reduce the yield strength ratio. At the same time, it introduces a large number of subgrain boundaries into the grains, which, together with oxide particles, serve as nucleation sites to promote the formation of ultrafine needle-like ferrite. Finally, it obtains L485M pipeline steel hot-rolled coil products with low yield strength ratio and high CTOD performance. Summary of the Invention

[0011] The purpose of this invention is to overcome the above-mentioned problems and provide an L485M pipeline steel coil with low yield strength ratio and high CTOD performance, and its manufacturing method. Its yield strength is 520~580MPa, tensile strength is 650~710MPa, yield strength ratio is ≤0.80, elongation is ≥30%, average impact energy at -60℃ is ≥300J, average drop shear area at -40℃ is ≥90%, and CTOD value at -40℃ is ≥1.60mm.

[0012] To achieve the above objectives, the present invention employs the following technical solution: A hot-rolled L485M pipeline steel coil with low yield strength ratio and high CTOD performance has the following chemical composition by weight percentage: C: 0.040%~0.060%, Si: 0.15%~0.25%, Mn: 1.60%~1.70%, P≤0.019%, S≤0.005%, Nb: 0.045%~0.055%, Ti: 0.012%~0.022%, Ni: 0.05%~0.10%, Als: 0.010%~0.020%, Ca: 0.002%~0.003%, Mg: 0.001%~0.002%, La: 0.001%~0.002%, N≤0.007%, with the balance being Fe and unavoidable impurities.

[0013] Hot-rolled coils have a yield strength of 520~580MPa, tensile strength of 650~710MPa, yield strength ratio ≤0.80, elongation ≥30%, average impact energy at -60℃ ≥300J, average drop shear area at -40℃ ≥90%, and CTOD value at -40℃ ≥1.60mm.

[0014] The thickness of the hot-rolled coil is 17.5~21mm, and the microstructure consists of polygonal ferrite + acicular ferrite + Mao islands.

[0015] This invention, without adding Mo and Cr, utilizes the concept of second-phase particle pinning and increased acicular ferrite nucleation sites. Through Mg-Ca-La-Ti microalloying, a large number of dispersed nanoscale composite oxide second-phase particles are introduced into the steel, suppressing austenite grain growth during billet heating and holding. A single-pass, low-speed, high-compression-ratio process is employed in the rough rolling stage to fully refine the austenite grains throughout the thickness direction. After rolling, a 15-25s relaxation followed by accelerated cooling allows the formation of dislocation substructures within the grains and the second-phase particles to provide numerous nucleation sites for ferrite, ultimately resulting in a fine polygonal ferrite + acicular ferrite microstructure. This achieves a good balance between hardness and softness, significantly reducing the yield strength ratio of the plate and greatly improving its low-temperature toughness, giving the plate and coil excellent CTOD performance.

[0016] The reasons for using the chemical components in this invention are as follows: Carbon (C) is the most fundamental and economical contributor to strength in steel, significantly enhancing yield strength and tensile strength primarily through interstitial solid solution mechanisms. However, its application in pipeline steel is strictly limited because increased carbon content drastically worsens weldability and low-temperature toughness. Higher carbon content leads to hardening of the weld heat-affected zone, increasing susceptibility to cold cracking. Simultaneously, carbon promotes the formation of harmful brittle phases such as pearlite, impairing the steel's crack-arresting toughness. Therefore, high-performance pipeline steels generally employ "ultra-low carbon" or "low carbon" designs. This invention controls the C content to 0.040%~0.060%.

[0017] Silicon (Si): During the smelting stage, silicon is a highly efficient deoxidizer, preferentially combining with oxygen in molten steel to form SiO2, thereby purifying the steel and reducing bubbles, which is crucial for ensuring the purity of the steel. In steel, silicon exists in the matrix in the form of substitutional solid solution, providing a significant solid solution strengthening effect and effectively improving strength. However, a high silicon content can significantly impair the weldability of steel, increasing the hardening tendency and cold cracking sensitivity of the weld heat-affected zone, and reducing the toughness of this area. Therefore, this invention controls the Si content to 0.15%~0.25%.

[0018] Mn: Manganese is a highly efficient solid solution strengthening element that can stably improve strength. Secondly, manganese can significantly lower the austenite-ferrite phase transformation temperature. This effect promotes the formation of fine acicular ferrite, bainite, and other low-temperature transformation structures during cooling. These structures have extremely high dislocation density and fine substructure, forming the microstructure basis for achieving high strength and high toughness in pipeline steel. Excessive manganese content will exacerbate center segregation in continuously cast billets, forming manganese-rich banded structures, severely deteriorating the transverse toughness of the steel. Therefore, this invention controls the Mn content to 1.60%~1.70%.

[0019] P, S, and N are impurity elements in steel. Ideally, their content should be as low as possible, but excessively low content will increase production costs. In this invention, P is ≤0.019%, S is ≤0.005%, and N is ≤0.007%.

[0020] Nb: During the high-temperature rolling stage, niobium, in the form of solid-solution atoms or fine Nb(C,N) precipitates, strongly inhibits the recrystallization of austenite grain boundaries and grain growth, allowing rolling to take place in the non-recrystallized austenite region, thus obtaining fine grains after phase transformation. During the subsequent cooling process, niobium precipitates in the matrix as extremely fine NbC nanoparticles, producing a significant precipitation strengthening effect. By precisely controlling the amount of niobium added and the process, an optimal combination of fine-grain strengthening and precipitation strengthening can be achieved, resulting in a significant increase in strength while simultaneously improving toughness. Therefore, this invention controls the Nb content to 0.045~0.055%.

[0021] Ti: Under low-alumina conditions, titanium can combine with oxygen in steel to form TiO, TiO2, and Ti2O3 particles, which have better high-temperature thermal stability than TiN. During continuous casting and heating, they effectively pin austenite grain boundaries, preventing excessive growth and providing a fine and uniform starting point for subsequent controlled rolling. Furthermore, the oxides can absorb Mn from the surrounding matrix, leading to the formation of a certain range of Mn-depleted regions around the particles, thereby promoting the nucleation of acicular ferrite. Therefore, this invention controls the Ti content to 0.012%~0.022%.

[0022] Ni: As an austenite stabilizing element, nickel can lower the phase transformation temperature and promote the formation of finer microstructures, thereby significantly improving the low-temperature impact toughness of steel. For thick-walled steel plates, nickel can effectively reduce the performance differences from the surface to the core, ensuring the uniformity and toughness of the microstructure throughout the cross-section. In this invention, the Ni content is controlled at 0.05%~0.10%.

[0023] Als: In pipeline steel smelting, aluminum is mainly used as a strong deoxidizer to remove dissolved oxygen from the molten steel, forming Al2O3 inclusions that float to the slag, thereby purifying the molten steel. However, excessive acid-dissolved aluminum can form large Al2O3 clusters, becoming crack initiation points or impairing toughness. Therefore, this invention controls the Al content to 0.010%~0.020%.

[0024] Ca: By feeding calcium wire into molten steel, high-melting-point, angular Al₂O₃ inclusions and easily deformable, elongated MnS inclusions can be transformed into low-melting-point, spherical calcium aluminate composite inclusions, thus refining the inclusion size. Furthermore, the spherical inclusions have minimal impact on anisotropy, improving properties in both the transverse and thickness directions. Therefore, this invention controls the Ca content to be between 0.002% and 0.003%.

[0025] Mg: Magnesium has a strong affinity for oxygen and sulfur in molten steel, effectively reducing their content. It also significantly modifies inclusions such as Al₂O₃ and MnS. The attraction between MgO particles is weaker than that between Al₂O₃ and Ti₂O₃ particles. Therefore, compared to Al₂O₃ and Ti₂O₃, MgO is less prone to agglomeration and growth, tending instead to be dispersed throughout the steel. It has a strong pinning effect on austenite grain boundaries and can also promote the formation of acicular ferrite. Therefore, this invention controls the Mg content to 0.001%~0.002%.

[0026] La: After the addition of magnesium and calcium, lanthanum can further modify inclusions in steel, forming small, dispersed spherical La2O3 and LaAlO3. These oxides have a low lattice mismatch with acicular ferrite, enhancing the ability of oxide particles to promote the nucleation of acicular ferrite. Therefore, the La content in this invention is controlled at 0.001%~0.002%.

[0027] A method for manufacturing L485M pipeline steel hot-rolled coils with low yield strength ratio and high CTOD performance includes smelting and continuous casting (hot metal pretreatment, converter smelting, ladle refining, LF furnace light desulfurization treatment, Mg-Ca-La-Ti composite treatment to control oxide morphology, RH furnace to control hydrogen and oxygen content, and slab continuous casting using electromagnetic stirring or dynamic light reduction), roughing, finishing, cooling, and coiling; specifically including: 1) Smelting and Continuous Casting: After hot metal pretreatment, a top-and-bottom blowing converter is used. Rapid decarburization and dephosphorization are achieved through optimized oxygen supply and bottom-blown argon. Mn, Nb, and Ni alloys are added for preliminary alloying. Ladle refining employs a light desulfurization process in an LF furnace. In the later stages of refining, Mg, Ca, La, and Ti alloys are added sequentially to control the quantity and morphology of inclusions, thereby improving plasticity and toughness. After composite treatment, bottom-blown argon is maintained in the ladle for soft stirring, promoting the full flotation of inclusions. The ladle is transferred to an RH station for vacuum circulation degassing, further improving the purity of the molten steel. During continuous casting, electromagnetic stirring is added to disrupt the dendrites in the primary solidified shell, improving surface and subsurface quality. Dynamic light pressure is applied to the solidifying billet in the fan-shaped section to reduce central porosity and improve the quality of the continuously cast billet.

[0028] 2) Rough Rolling: A 200mm thick continuously cast billet is heated to 1160~1190℃ in a walking beam furnace and held for 160~300min, followed by five passes of rough rolling. To achieve a high reduction ratio in the second to fourth passes, the reduction rate in the first pass is controlled below 9%, and the reduction rates in the second to fourth passes are all greater than 27%, with a total reduction rate of 71%~72%. The intermediate billet thickness is 56~57mm. Furthermore, the rough rolling speed in the first pass is controlled below 1.7m / s, and the speeds in the second to fifth passes are controlled below 2.6m / s. The final rolling temperature is controlled at 970~1000℃ to ensure it is within the austenite recrystallization zone and to prevent mixed grain formation. The high reduction ratio and low rolling speed in the rough rolling stage allow for sufficient dynamic recrystallization of the austenite grains from the surface to the core, achieving the goal of refining the original austenite grains and improving the uniformity of the microstructure. The austenite with an average grain size of 13~25μm obtained by this rough rolling process achieves ultrafine recrystallized austenite and reduces the dependence on the addition of Mo and Cr alloying elements.

[0029] 3) Finishing Rolling: The intermediate slab employs accelerated cooling to significantly shorten the waiting time for rolling, preventing backheating and austenite grain growth. The finishing rolling inlet temperature is controlled between 910 and 970℃. The finishing rolling process uses a seven-pass design, with each pass having a reduction rate greater than 7%, resulting in a total reduction rate of 61% to 69%. During finishing rolling, the reduction rate is controlled to gradually increase the deformation resistance with each pass, ensuring sufficient flattening of the austenite grains and dislocation accumulation within the grains to improve strength. The final rolling temperature is controlled between 735 and 790℃.

[0030] 4) Cooling and Coiling: After rolling, a short relaxation period of 15-25 seconds is performed. During relaxation, the dislocations stored within the austenite recover and form more regular and stable subgrain boundaries, providing more nucleation sites for the subsequent acicular ferrite phase transformation and promoting the formation of ultrafine grains. Furthermore, a small amount of polygonal ferrite soft phase is formed during relaxation. The coordinated deformation of the soft and hard phases significantly reduces the yield strength ratio and improves uniform deformation capability. After relaxation, ultra-fast cooling combined with laminar flow cooling is used. The initial cooling temperature is controlled at 730-750℃, the ultra-fast cooling rate is 50-70℃ / s, and the laminar flow cooling rate is 10-20℃ / s. After cooling, a high-strength coiler is used for coiling, with the coiling temperature controlled at 300-420℃.

[0031] This invention employs a Mg-Ca-La-Ti composite treatment method during the smelting stage to introduce a large number of nano-sized oxide particles, which pin austenite grain boundaries during heating and holding to prevent grain growth. During the rough rolling stage, increasing the compression ratio and reducing the speed promotes sufficient recrystallization of austenite grains from the surface to the core, providing a fine original structure for subsequent phase transformation. After rolling, a short relaxation time is performed, which introduces a small amount of polygonal ferrite to reduce the plate's yield strength ratio and promotes the formation of subgrain boundaries, which, together with the oxide particles inside the austenite grains, provide a large number of sites for the nucleation of acicular ferrite. Ultimately, a product with high strength, low yield strength ratio, and excellent low-temperature CTOD performance is obtained, making it safer during service in low-temperature environments.

[0032] Compared with the prior art, the beneficial effects of the present invention are: 1) The Mg-Ca-La-Ti composite treatment method introduces a large number of nano-sized oxide particles into the steel, which hinders the growth of austenite grains during the heating and holding process of the billet. Therefore, even at higher heating temperatures, fine austenite grains can be obtained, reducing the mill load and facilitating the implementation of roughing rolling with a large compression ratio.

[0033] 2) By increasing the compression ratio per pass in the roughing stage and reducing the rolling speed, sufficient dynamic recrystallization of austenite grains from the surface to the core is achieved, resulting in an average austenite grain size of 13~25μm. Grain refinement is achieved without adding Mo and Cr elements, giving the product a certain economic advantage.

[0034] 3) After rolling, a short relaxation time is used to promote the formation of a small amount of polygonal ferrite. Through the coordinated deformation of soft and hard phases, the yield strength ratio of the plate and coil is significantly reduced, so that the product has better resistance to large plastic deformation.

[0035] 4) The oxide particles formed during the smelting process and the subgrain boundaries formed during the relaxation process together provide a large number of nucleation sites for the acicular ferrite phase transformation during the cooling stage, promote the formation of ultrafine acicular ferrite structure, and give the product excellent low-temperature CTOD performance. Attached Figure Description

[0036] Figure 1 The image shows the morphology of the rough-rolled austenite grains in Example 1.

[0037] Figure 2 The microstructure of Example 1 consists of polygonal ferrite (PF) + acicular ferrite (AF) + Mao islands (M / A). Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the specific implementation methods of this invention will be further described below in conjunction with the embodiments. The following embodiments are used to specifically illustrate the content of this invention. These embodiments are only general descriptions of the content of this invention and do not limit the content of this invention.

[0039] The chemical composition of Examples 1-10 is shown in Table 1, the heating, rolling and cooling process parameters are shown in Tables 2 and 3, and the mechanical property test results are shown in Table 4.

[0040] Table 1. Chemical composition (wt%) of the steel in the examples

[0041] Table 2 Heating and roughing process regimes for each embodiment

[0042] Table 3. Finishing and cooling process procedures for each embodiment.

[0043] Table 4 Main mechanical properties of each embodiment

[0044] As can be seen from Tables 1-4, by adopting the composition design, rolling and cooling process of the present invention, hot-rolled pipeline steel coils with low yield strength ratio and high CTOD performance at the 485MPa level can be produced.

[0045] The purpose of this invention is to provide an L485M pipeline steel coil with low yield strength ratio and high CTOD performance, and its production method. This invention employs a C-Mn-Nb-Ni design. Without adding Mo and Cr, a Mg-Ca-La-Ti composite treatment method is used during smelting to introduce nano-sized oxide particles that pin austenite grain boundaries during the heating and holding stages of the cast billet, providing a uniform and fine initial microstructure for rolling. In the rough rolling stage, the single-pass compression ratio is increased and the rolling speed is reduced, allowing sufficient recrystallization of austenite from the surface to the core. This refinement of austenite grains improves its overall mechanical properties. A short relaxation time is used after rolling to obtain an ultrafine-grained acicular ferrite microstructure, significantly reducing the yield strength ratio of the coil while greatly improving low-temperature toughness, ultimately achieving a production method for L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance.

Claims

1. A hot-rolled coil of L485M pipeline steel with low yield strength ratio and high CTOD performance, characterized in that, The chemical composition of the steel, by weight percentage, is as follows: C: 0.040%~0.060%, Si: 0.15%~0.25%, Mn: 1.60%~1.70%, P≤0.019%, S≤0.005%, Nb: 0.045%~0.055%, Ti: 0.012%~0.022%, Ni: 0.05%~0.10%, Als: 0.010%~0.020%, Ca: 0.002%~0.003%, Mg: 0.001%~0.002%, La: 0.001%~0.002%, N≤0.007%, with the balance being Fe and unavoidable impurities.

2. The L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance according to claim 1, characterized in that, Hot-rolled coils have a yield strength of 520~580MPa, tensile strength of 650~710MPa, yield strength ratio ≤0.80, elongation ≥30%, average impact energy at -60℃ ≥300J, average drop shear area at -40℃ ≥90%, and CTOD value at -40℃ ≥1.60mm.

3. The L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance according to claim 1, characterized in that, The thickness of the hot-rolled coil is 17.5~21mm, and the microstructure consists of polygonal ferrite + acicular ferrite + Mao islands.

4. A method for manufacturing L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance as described in any one of claims 1-3, comprising smelting and continuous casting, roughing, finishing, cooling and coiling; characterized in that, Specifically, it includes: 1) Continuous casting: Mg, Ca, La, and Ti alloy wires are added sequentially in the later stage of refining; 2) Rough rolling: The continuously cast billet is heated to 1160~1190℃ and held for 160~300min, followed by five passes of rough rolling. The reduction rate of the first pass is controlled below 9%, and the reduction rate of the second to fourth passes is greater than 27%, with a total reduction rate of 71%~72%. In addition, the rough rolling speed of the first pass is controlled below 1.7m / s, and the rough rolling speed of the second to fifth passes is controlled below 2.6m / s. The final rolling temperature of the rough rolling is controlled at 970~1000℃. 3) Finishing rolling: The entry temperature of the finishing rolling mill is controlled at 910~970℃; the total reduction rate is 61%~69%; the final rolling temperature of the finishing rolling mill is controlled at 735~790℃; 4) Cooling and coiling: After rolling, relax for 15~25s. After relaxation, use ultra-fast cooling + laminar flow cooling. The starting cooling temperature is controlled at 730~750℃, the ultra-fast cooling rate is 50~70℃ / s, and the laminar flow cooling rate is 10~20℃ / s. The coiling temperature is controlled at 300~420℃.

5. The method for manufacturing L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance according to claim 4, characterized in that, The smelting and continuous casting process also includes: after hot metal pretreatment, a top and bottom blowing converter is used, and the ladle is refined using LF furnace light desulfurization treatment; after composite treatment, the bottom blowing argon gas in the ladle is kept for soft stirring, and the ladle is transferred to the RH station for vacuum circulation degassing treatment of the molten steel; electromagnetic stirring is added during the continuous casting process.

6. The method for manufacturing L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance according to claim 4, characterized in that, The average austenite grain size in the steel after rough rolling is 13~25μm.

7. The method for manufacturing L485M pipeline steel hot-rolled coil with low yield strength ratio and high CTOD performance according to claim 4, characterized in that, The thickness of the intermediate slab between the finishing and roughing rolling processes is 56~57mm.

Citation Information

Patent Citations

  • Subsea pipeline steel plate coil with excellent low-temperature CTOD performance and production process thereof

    CN111979497A

  • Subsea pipeline steel L485MO with low yield ratio and low hardness and production method thereof

    CN113278880A

  • Thick high-strength and high-toughness L485M pipeline steel and production method thereof

    CN115449709A

  • Low-yield-ratio X70-grade pipeline steel hot-rolled coiled plate and manufacturing method thereof

    CN116970870A

  • High-performance X70M pipeline steel for thick-wall spiral seam submerged arc welding steel pipe and manufacturing method of high-performance X70M pipeline steel

    CN117987741A